A Simulation-Based Decision Making Framework for the Anticipatory Change Planning of Intralogistics Systems - Mustafa Güller; Tobias Hegmanns; Michael Henke; Natalia Straub (Innovative Methods in Logistics and Supply Chain Management: Current Issues and Emerging Practices. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 18, 2014)
In many industries flexibility and changeability are becoming a more important characteristic for providing responses to fluctuating conditions without significant loss in time, costs and efforts. In order to cope with turbulences and the increasing level of unpredictability, future intralogistics systems have to feature short reaction times, high flexibility in processes and the ability to adapt to frequent changes. However, the flexibility planning of the design and operations of intralogistics systems as a mean for improved supply chain agility has been ignored. There are many forecasting methods in the literature that can be used to predict future conditions, such as market development, product portfolio or future customer expectations. Nevertheless, analyzing the impact of these forecasts on the performance and costs measures of intralogistics systems is still experiencing insufficient methodical and tool support. Anticipatory change planning can be a usable approach for managers to make contingency plans for intralogistics systems to deal with the rapidly changing marketplace. In this context, this paper proposes a simulation-based decision framework for the anticipatory change planning of intralogistics systems in order to cope with unpredictable events in the future. This approach includes the quantitative assessments based on the simulation in defined scenarios as well as the analysis of performance availability in terms of the degree of fulfillment of customer requirements. The implementation of the approach is illustrated on a new intralogistics technology called the Cellular Transport System.
10419/209188; https://econpapers.repec.org/RePEc:zbw:hiclpr:19
Keywords: 650; anticipatory change planning; performance availability; flexibility; simulation